The Use of Self-Assessment in Teaching Writing Report Text to the Eleventh Grader of SMAN 1 Taman Sidoarjo (RETAIN, 2018)
Abstrak Masalah siswa dalam penulisan adalah siswa masih bingung dalam memutuskan apa yang harus ditulis dan bagaimana menulis karena siswa tidak tahu kriteria penulisan dan komponen penulisan. Teknik yang tepat adalah menggunakan Self Assessment atau penilaiana diri karena self assessment sesuai untuk memecahkan masalah ini. Dengan self assessment, siswa membangun kesadaran pada tulisan mereka dan meningkatkan kemapuan keteramp[ilan menulis mereka, kemampuan metacognitif mereka, tanggung jawab pekerjaan siswa, berpikir kritis pemecahan masalah. Penilitian ini dilakukan untuk mendeskripsikan penggunaan self assessment, tugas menulis siswa selama penggunaan self assessment dan respon siswa melalui self assessment. Peneliti juga menggunakan metode kualitatif sebagai desain penelitian. Hasilnya menunjukkan bahwa penggunaan self assessment diimplementasikan sejalan dengan mengikuti siklus dirumuskan oleh H.McMillan dan Hearn (2008). Guru dapat membantudan mengelola siswa menggunakan self assessment dengan baik. Maka proses pembelajaran dapat dilakukan sesuai dengan yang diharapkan. Para siswa dapat menghasilkan tugas yang baik. Disamping itu, penggunaan penilaian diri membantu siswa mengetahui kelemahan merek dan keslahan mereka. Namun guru juga memberikan umpan balik kepada siswa sambil mengikuti target kriteria dan hasil tulisan siswa.Kata Kunci: Self assessment, teks laporan, pembelajran menulis AbstractStudents’ problems of writing are students still confused in deciding what to write and how to write because students do not know the criteria of writing and the components of writing. The appropriate technique is using self assessment because self assessment is suitable to solve this problem. While self assess, students build student’s awareness on their writing, students also train their self to self assess on their writing and improve their writing skill ability, metacognitive skill, responsibility of students’ work, critical thinking and sense of mathematic problem – solving. This study was conducted to describe the use of self assessment, the students’ writing task during the use of self assessment and students’ responses through self assessment. The researcher used qualitative method as a research design. The result showed that the use of self assessment implemented in line with following the cycled process by H. McMillan and Hearn (2008). The teacher could help and managed the students using self assessment well then the learning process could do as expected. The students could product the good task and the use of self assessment helps the students know their weakness and their mistakes. The students also could realize their mistakes and correct their mistakes by them self. And then, the students not repeat their mistakes.However the teacher also gave the feedback to students while following the criteria targets and students’ writing product.Keywords: Self assessment, report text, teaching writing